PENGARUH ROLLING MASSAGE TERHADAP KELANCARAN PRODUKSI ASI IBU POST PARTUM - Vitria Komala Sari; Widya Nengsih; Ainal Mardiah; Sari Ida Miharti (Maternal Child Health Care, 2023)
At Begins at the 5th and 6th nerves and ends at the scapula, speeding up the action of the parasympathetic nerves in conveying signals to the anterior and posterior brain, allowing oxytocin and prolactin to be released. The researchers want to see how the husband's Rolling Massage affects the smooth production of postpartum mother's milk in the Mercu Public Health Center's working region in Sangir Balai Janggo District, South Solok Regency. A quasi-experimental design with a post-test only control group is used in this sort of study. The research was carried out between November 2022 and January 2023. The participants in this study were all postpartum women who were in the Mercu Health Center's operating region, and a purposive selection approach was used to choose a sample of 32 persons. The observation sheet for the smooth production of breast milk on days 1-4 was employed as the instrument. The Mann-Whitney Test was used to analyze the data. The study's findings revealed that p = 0.000, indicating that there is an effect of rolling massage by the husband on the smooth production of breast milk for postpartum mothers, with smooth production of breast milk in the treatment group on days 1-4, namely 18.8 percent, 62,5 percent, 93.8 percent, 93.8 percent, and smooth production of breast milk in the control group on days 1-4, namely 37.5 percent, 50 percent, and smooth production of breast milk on days 2-3, namely 37.5 percent. The conclusion is that the husband's Rolling Massage has a substantial influence on the smooth production of postpartum mother's milk. Husbands should be allowed to perform Rolling Massage on postpartum women to ensure that milk supply continues smoothly after childbirth, according to researchers.Keywords : Rolling massage, milk production that is smooth